Effect of grilling and roasting on formation of Cholesterol Oxidation Products (COPs) in chicken and mutton - Alina A.R.; Nurul Farah Sakinah A.; Shazamawati Z.H.; Thema Juhana M.J.; Siti Mashitoh A.; Ummi Syuhada H.S.; Nurul Mawaddah A.H.; Nurulhuda S. (2024)
Indexed by SCOPUS